Awareness of Security Threats in Social Media - et. al., Alaa Alsubhi, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Social media are sites on the Internet that allow users to interact and communicate with each other and since it is easy to use and produce a fast way to communicate. According to these features, it becomes very popular to everyone either the young generation or the old generation. But we need to be concerned about security and privacy. Is our information safe? Will we be safe while we using these sites? This paper presents the reasons that make us unsafe in social media. We'll also show some of the ways that we should follow to protect ourselves. So, in short, we can say that this research aims to increase the awareness of the risks of social media threats. Also, suggest some solutions to reduce the damage that may happen